Cost-effectiveness and Quality of Specialized and Routine Care in a German Cohort of Patients with Chronic Pruritus - Svenja Müller; Sonja Ständer; Mandy Naatz; Matthias Augustin; Sabine Steinke (Medical Journals Sweden, 2023)
Chronic pruritus is a prevalent interdisciplinary symptom with a strong influence on health-related quality of life. Patients need extensive diagnostics and long-term treatment. This retrospective and prospective cohort study compared routine and university-based specialized care in terms of cost-effectiveness and patient benefit. Direct medical and non-medical costs and patient-reported outcomes (PRO; pruritus intensity, quality of life, treatment needs and benefits) were assessed. Data analyses were conducted using descriptive methods and non-parametric statistical tests. A total of 300 adult patients (54.3% female) participated in the study. Six months after the treatment start in a specialized German pruritus care unit, the total costs were significantly reduced (mean total costs 686 € vs 433 € per patient per half year (total cohort); p <  0.001; mean out-of-pocket costs 198 € vs 124 € per half year (total cohort), p <  0.001). Pruritus intensity (numerical rating  scale 5.3 vs 3.7, p < 0.001), quality of life (Dermatology Life Quality Index 8.9 vs 5.7, p < 0.001) and patient benefit (Patient Benefit Index Pruritus 1.2 vs 2.1, p < 0.001) improved significantly (total  cohort). The results of this study show, that treatment of chronic pruritus patients in a specialized itch centre leads to an improvement in patient  benefit and reduces the economic burden at the same time.